Metabolitos secundarios de los géneros Duguetia, Guatteria, Unonopsis y Xylopia, familia Annonaceae con relación a su hábitat de la estación Allpahuayo -Mishana y Puerto Almendra, Loreto - Perú - Arévalo García, Meri Nancy (2021)
The present investigation consisted of carrying out the phytochemical analysis and determining the relationship with their habitat, of the genera of the Annonaceae, Duguetia, Annona, Unonopsis and Xylopia families, in relation to their Habitat, from the Allpahuayo - Mishana Station and Puerto Almendra. The analysis was carried out in the Laboratory of the Natural Resources Research Center of the Amazon-CIRNA of the UNAP. The collected samples were taxonomically identified in the Amazon Herbarium of the UNAP for their respective qualitative and quantitative study. The phytochemical analysis determined the presence of secondary metabolites for the genus Xylopia coumarins, steroids, flavonoids, phenols and quinones, of coumarins, triterpenes and saponin. Quinones, triterpenes, quaternary bases and steroids were found for the genus Unonopsis. Quaternary bases, alkaloids, and triterpenes, in the case of Duguettia, there is the presence of quinones.In this context, it is determined that the production of secondary metabolites in plants in general and specifying in the Annonaceae family, is influenced by the environment factor, which provides the conditions for the production of metabolites and allows the plant to have the general capacity to survive and overcome local challenges, allowing them to interact with their environment.